Integration of Religious Moderation Values Through the Rahmatan Lil Alamin Student Profile Project - Minarti, Sri; Wardi, Moh; Efendi, Moh. Yusuf; Wahdani, Firda Rizka Rachma; Mohd Raus, Norakyairee (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
This research aims to analyze the developmental characteristics of students through the values of religious moderation within the Rahmatan lil Alamin Student Profile Project at MIN 1 Bojonegoro and MINU Unggulan Sukorejo. The methodology employed involves a qualitative approach utilizing a qualitative descriptive research design. Data collection was carried out through observation techniques, in-depth interviews and documentation. Data analysis is aligned with the conceptual framework established by Miles and Huberman. The results of this research reveal that the integration of religious moderation values ​​in the Rahmatan Lil Alamin Student Profile Project at MIN 1 Bojonegoro and MINU Unggulan Sukorejo can be achieved effectively in strengthening the positive character of students in Phases A, B and C. In the 2023 academic year /2024, strengthening the character of students at MIN 1 Bojonegoro focuses on the values ​​of religious moderation, civility (Ta'adub) and the value of deliberation (Syura), while at MINU Unggulan, it includes the value of equality (musawah), the value of tolerance (tasamuh), and dynamic and innovative values ​​(tathawwur wa ibtikar). MIN 1 Bojonegoro integrates the values ​​of religious moderation through an environmental care approach, while MINU Unggulan uses the traditional Ahlusunnah wal Jama'ah an-Nahdliyah approach.